NURSE EDUCATOR COMPETENCIES IN DEVELOPING MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) POLICY - Dhawo, Maria Silvana; Dias, Maria Frani Ayu Andari (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) has been integrated into the Indonesian higher education system since 2020. While nursing study programs are not mandated to participate in MBKM activities, they are still required to meet the key performance indicators outlined by the Ministry of Education and Culture through the MBKM program. To ensure that students receive valuable learning experiences in line with outcome-based curricula, nurse educators must possess additional competencies in designing learning experiences and coordinating collaborations with various stakeholders. This will equip nursing graduates to meet the demands of the modern era and compete globally, while also addressing the needs of society. Currently, the required competencies for nurse educators and the specific roles and responsibilities necessary to fulfill the MBKM policy have not been clearly defined. This article aims to elucidate the core competencies of nursing lecturers and the implementation of the expected roles and responsibilities essential for the successful execution of the MBKM program.